Circular RNA circ_0007841 participates in progression of nonsmall cell lung cancer via miR-199a-5p/SphK2 axis. Issue 10 (5th September 2022) - Long, Feihu; Li, Zifan; Wei, Zichun; Xie, Yuancai
Abstract : CircRNAs have been found to be participated in the development of numerous cancers. Nevertheless, the role of circRNAs in the progression of nonsmall cell lung cancer (NSCLC) has not been fully made clear. The purpose of our study was to study and understand the mechanism of circ_0007841 regulating the progression of NSCLC. NSCLC tissue samples and adjacent normal tissue samples used were obtained from 53 NSCLC patients. The expressions of circ_0007841, miR-199a-5p and SphK2 in all samples were detected by the real-time quantitative PCR. Then luciferase reporter gene assay and RNA immunoprecipitation (RIP) assay were used to analyze the relevance between circ_0007841, miR-199a-5p and SphK2. Cell Counting Kit-8, colony-forming, thymidine analog 5-ethynyl-2′-deoxyuridine assays, and transwell assay detect the effects of these three biomolecules on NSCLC carcinogenesis by western blot. We evaluate the effect of circ_0007841 on the growth of NSCLC by establishing the xenograft mice model. Experimental studies have shown that the higher expression of circ_0007841 in NSCLC tissues, and circ_0007841 strengthen cell viability, cell proliferation and cell adhesion. In addition, miR-199a-5p exerts an inhibitory effect in NSCLC cells by inhibiting SphK2. And Sphk2 regulates cell proliferation and adhesion. In addition, in-vivo silencing of circ_0007841 was found to inhibit the growth of NSCLC tumors. This research demonstrated that circ_0007841 had a positive influence in improving NSCLC development by targeting miR-199a-5p and upregulating oncogene SphK2.